2004
DOI: 10.1002/ajh.20117
|View full text |Cite
|
Sign up to set email alerts
|

ABL oncogene amplification with p16INK4a gene deletion in precursor T‐cell acute lymphoblastic leukemia/lymphoma: Report of the first case

Abstract: Gene amplification is a relatively rare event in hematologic malignancies. The ABL gene on chromosome band 9q34 is a proto-oncogene and is the well-known translocation partner of the BCR gene on 22q11 giving rise to t(9;22)(q34;q11), which is the hallmark of chronic myeloid leukemia and is the most common chromosomal abnormality in adult acute lymphoblastic leukemia (ALL). Amplification of ABL is an exceedingly rare event, with only less than 5 cases reported in the literature. The p16 INK4a (or CDKN2A) gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…We identify a novel mechanism by which Abl kinases are constitutively activated in breast cancer cells. Unlike in leukemia where Abl kinases are activated by translocation or gene amplification (8,9), in breast cancer cells, Abl kinases are activated downstream of deregulated EGFR, HER-2, and Src kinases. Taken together, our findings are highly significant because they indicate that Abl kinases are likely to act downstream of ErbB and Src kinase signaling pathways to drive breast cancer cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identify a novel mechanism by which Abl kinases are constitutively activated in breast cancer cells. Unlike in leukemia where Abl kinases are activated by translocation or gene amplification (8,9), in breast cancer cells, Abl kinases are activated downstream of deregulated EGFR, HER-2, and Src kinases. Taken together, our findings are highly significant because they indicate that Abl kinases are likely to act downstream of ErbB and Src kinase signaling pathways to drive breast cancer cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In 95% of patients with chronic myelogenous leukemia (CML), Abl1 is translocated next to the BCR gene [t (9;22)], generating a BCR-Abl fusion protein that has constitutively active tyrosine kinase activity (8). Abl1 and Abl2 also are translocated next to the Tel gene (Ets family transcription factor) in leukemia and myeloproliferative diseases, and Abl1 is amplified in T-cell acute lymphocytic leukemia (8,9). Hematopoietic cells expressing BCR-Abl display decreased adhesiveness to bone marrow stroma and an increased ability to survive, proliferate, migrate, and invade (8,10).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of Cterminal DNA-binding motifs and nuclear localization signals in c-Abl enables shuttling between cytoplasmic and nuclear compartments, extending the exposure to additional Abl kinase substrates (Wen et al, 1996;Taagepera et al, 1998;Yoshida et al, 2005). The activated forms of Abl kinases (BCR-Abl, Tel-Abl and Tel-Arg) induce the development of human leukemia (Skorski et al, 1998;Druker et al, 2001;Pendergast, 2001;Kim et al, 2004). Recent studies suggest that Abl kinases are constitutively activated in breast cancer cells and constitutive activation of Abl kinases promotes breast cancer cell invasion (Srinivasan and Plattner, 2006;Jallal et al, 2007;Srinivasan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike homozygous deletion, hemizygous deletion might not be sufficient to turn off the function of involved genes (CDKN2A and CDKN2B). On the other hand, Kim et al [27] suggested that homozygous deletion is a poor prognostic factor in adult but not in childhood ALL. Kuchinskaya et al [12] reported that there was no significant difference in outcome between cases with or without 9p21 deletion or between cases with hemi or homozygous deletion of 9p21.…”
Section: Discussionmentioning
confidence: 99%